206k views
2 votes
What is the answer to this question?

What is the answer to this question?-example-1
User Nadirah
by
4.5k points

1 Answer

2 votes

Answer:

Quadratic: y = -x^2 + 7

Explanation:

Diff Diff Diff in

in x x y in y Differences

-2 3

1 -1 6 3

1 0 7 1 -2

1 1 6 -1 -2

1 2 3 -3 -2

The differences in x are all 1. The differences in y are not equal, so it is not linear. The differences in the differences in y are all 2. It is quadratic.

Try: y = -x^2 + 7

x = -2:

y = -(-2)^2 + 7 = -4 + 7 = 3

You get (-2, 3) which is a given point.

Now try the same x value with the other quadratic equation.

y = x^2 + 7

x = -2:

y = (-2)^2 + 7 = 4 + 7 = 11

You get (-2, 11) which is not a given point.

Answer:

Quadratic: y = -x^2 + 7

User Amplifier
by
4.7k points